Penyakit Gagal Ginjal Kronis Stadium 5 Berdasarkan Determinan Umur, Jenis Kelamin, dan Diagnosa Etiologi di Indonesia Tahun 2018 - Syahrul Hamidi N; Sofyan Musyabiq (Medula, 2021)
Chronic kidney failure has become a very important issue in recent years due to its increasing frequency and the high costs associated with it is increasingly being seen as a major public health problem associated with premature death with important social and economic implications. In addition to early diagnosis and detection, knowledge related to the causes of hemodialysis patient mortality in Indonesia in 2018 can be used as scientific evidence in planning, program implementation, program evaluation, and determining the priority scale of the hemodialysis patient mortality prevention program in Indonesia, which is the aim of this study. . This type of research is literature review research. The target population is all hemodialysis patients in Indonesia. The affordable population in this study were all hemodialysis patients recorded in the 2018 Indonesian Renal Registry (IRR) data set. The sample of this study was all hemodialysis patients (total sampling) recorded in the 2018 Indonesian Renal Registry data set. Incidence of 3 months of mortality in new HD patients amounted to 31.7%. Age> 60 years, hemoglobin <8 g / dl, serum albumin <3.5 g / dl, ECG abnormalities, and femoral access were significant predictors of mortality in the first 3 months of HD. The comorbid conditions associated with the mortality of CKD patients undergoing hemodialysis are age, coronary heart disease, congestive heart failure, stroke, sepsis, tuberculosis, and pneumonia.